Frontal brain asymmetry, childhood maltreatment, and low-grade inflammation at midlife. (January 2017) - Hostinar, Camelia E.; Davidson, Richard J.; Graham, Eileen K.; Mroczek, Daniel K.; Lachman, Margie E.; Seeman, Teresa E.; van Reekum, Carien M.; Miller, Gregory E.
Highlights: Resting frontal EEG asymmetry was significantly associated with inflammation. Childhood maltreatment moderated frontal asymmetry's associations. Findings support the diathesis-stress model of frontal brain asymmetry. Abstract: Frontal EEG asymmetry is thought to reflect variations in affective style, such that greater relative right frontal activity at rest predicts enhanced emotional responding to threatening or negative stimuli, and risk of depression and anxiety disorders. A diathesis-stress model has been proposed to explain how this neuro-affective style might predispose to psychopathology, with greater right frontal activity being a vulnerability factor especially under stressful conditions. Less is known about the extent to which greater relative right frontal activity at rest might be associated with or be a diathesis for deleterious physical health outcomes. The present study examined the association between resting frontal EEG asymmetry and systemic, low-grade inflammation and tested the diathesis-stress model by examining whether childhood maltreatment exposure interacts with resting frontal asymmetry in explaining inflammation. Resting EEG, serum inflammatory biomarkers (interleukin-6, C-reactive protein, and fibrinogen) and self-reported psychological measures were available for 314 middle-aged adults (age M = 55.3 years, SD = 11.2, 55.7% female). Analyses supported the diathesis-stress model and revealed that resting frontal EEG asymmetry was significantly associated with inflammation, but only in individuals who had experienced moderate to severe levels of childhood maltreatment. These findings suggest that, in the context of severe adversity, a trait-like tendency towards greater relative right prefrontal activity may predispose to low-grade inflammation, a risk factor for conditions with inflammatory underpinnings such as coronary heart disease.